The Poentianak of Pegangsaan: News Framing and the Dutch Media Sentiment Against Indonesian Nationalism in 1928 - Andriawan, Tatag Nasrul (Lembaran Sejarah, 2025)
This paper attempts to analyze news framing of a crowd-drawing incident that occurred in Pegangsaan in January 1928, where the alleged supernatural abduction of an eight-year-old became a media sensation. By utilizing historical methods and news framing analysis on the coverage of the incident in Dutch-language publications issued in Indonesia and the Netherlands, I found that some Dutch newspapers portrayed this incident as indicative of Indonesian societal backwardness. They suggested that beliefs in superstitions are evidence of the supposed incapability of native Indonesians to self-govern—a sentiment aimed at undermining the increasingly prominent Indonesian nationalist movements and justifying the continuation of Dutch colonialism in Indonesia. I argue that this deliberate framing of the incident also reinforced the premise of colonialism as a “civilizing mission,” which positioned the Dutch colonial rule as a fundamental element for educating and liberating the native population from their “backwardness.” Ultimately, this paper explores how certain Dutch newspapers instrumentalized cultural stereotypes to delegitimize Indonesian nationalism and maintain Dutch colonial authority.